Strategi Pengelolaan Limbah Infus Infeksius di Rumah Sakit Umum Daerah (RSUD) H. Abdul Manap Kota Jambi - Alfarizky, Agung; Yanova, Shally; Viareco, Hariestya (Jurnal Pelita Teknologi, 2023)
Hospitals are one of the places that produce waste, one of which is infectious medical waste. Infectious waste is an object that is then categorised as waste after contact with pathogenic organisms that have the potential to transmit disease to humans. Hospital waste management is needed for the comfort and cleanliness of the hospital environment, because it can prevent health problems. The first objective of this study was to evaluate the suitability of infectious medical waste management at the Regional General Hospital (RSUD) H. Abdul Manap Jambi City with the Regulation of the Minister of Health of the Republic of Indonesia Number 7 of 2019 concerning Hospital Environmental Health which regulates all forms of activities and health in the hospital environment. The second objective was to determine infectious medical waste management strategies using the SWOT analysis method to determine the strengths, weaknesses, opportunities, and threats that exist, so that strategies can be determined to optimise the management of infectious medical waste. The results of the research obtained are that there are several stages in the management of infectious medical waste that are not in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 7 of 2019. Then, based on the results of the SWOT analysis, it is known that the IFAS and EFAS values for infectious medical waste management at RSUD H. Abdul Manap Jambi City are in quadrant I, which explains that the strategy that must be used to optimise medical waste management is the S-O strategy. The S-O strategy is a strategy that relies on strengths and opportunities, so the implementation of this S-O strategy is structured based on the strengths and opportunities possessed by the H. Abdul Manap Hospital Jambi City in carrying out infectious medical waste management.